Towards an Asian economic community vision of a new Asia - Kumar, Nagesh 1958- (Institute of Southeast Asian Studies, 2004)
Contributed papers presented at the International Conference on 'Building a New Asia: Towards Asian Economic Community,' on 10-11 March, 2003, at New Delhi.